Quantification of pulmonary perfusion using LSIM-CT correlates with pulmonary hemodynamics in patients with CTEPD - Yamaguchi, Tomohiro; Ehara, Shoichi; Yoshida, Hisako; Himoto, Daisuke; Izuta, Shinichiro; Hayashi, Ou; Hayashi, Hiroya; Ogawa, Mana; Shibata, Atsushi; Yamazaki, Takanori; Izumiya, Yasuhiro; Fukuda, Daiju (Frontiers in Cardiovascular Medicine, 2023)
Background: Lung subtraction iodine mapping (LSIM)-CT is clinically useful technique, which can visualize the pulmonary mal-perfusion in patients with chronic thromboembolic pulmonary disease (CTEPD). However, little is known about the associations of LSIM images with hemodynamic parameters of patients with CTEPD. This study was performed to investigate a parameter of LSIM images associated with mean pulmonary arterial pressure (mPAP), and to validate the association between the pulmonary vascular resistance, right atrial pressure, cardiac index, and exercise capacity in patients with CTEPD. Methods: This single-center, prospective observational study involved 30 patients diagnosed with CTEPD using lung perfusion scintigraphy. To examine the correlation of decreased pulmonary perfusion area (DPA) with mPAP, areas with 0 to 10 HU, 0 to 15 HU, 0 to 20 HU, 0 to 30 HU in lung subtraction images were adopted in statistical analysis. The DPA to total lung volume ratio (DPA ratio, %) was calculated as the ratio of each DPA volumes to the total lung volume. To assess the correlation between DPA ratios of 0 to 10 HU, 0 to 15 HU, 0 to 20 HU, 0 to 30 HU and mPAP, Spearman's rank correlation coefficient was used. Results: DPA ratio of 0-10 HU had the preferable correlation with mPAP than DPA ratios of 0 to 15 HU, 0 to 20 HU, 0 to 30 HU (ρ=0.440, P = 0.015). DPA ratio of 0-10HU had the significant correlation with pulmonary vascular resistance (ρ=0.445, P = 0.015). The receiver operating characteristic curve analysis indicated that the best cutoff value of the DPA ratio of 0-10HU for prediction of an mPAP of ≥30 mmHg was 8.5% (AUC, 0.773; 95% CI, 0.572–0.974; sensitivity, 83.3%; specificity, 75.0%). Multivariate linear regression analysis, which was adjusted for the main pulmonary arterial to ascending aortic diameter ratio and right ventricular to left ventricular diameter ratio, indicated DPA ratio of 0-10HU was independently and significantly associated with mPAP (B=89.7; 95% CI, 46.3-133.1, P < 0.001). Conclusion: The DPA ratio calculated by LSIM-CT is possibly a useful parameter to estimate the hemodynamic status in patients with CTEPD.